2014
DOI: 10.1175/jpo-d-13-062.1
|View full text |Cite
|
Sign up to set email alerts
|

On the Warm Water Volume and Its Changing Relationship with ENSO

Abstract: The interannual, equatorial Pacific, 20°C isotherm depth variability since 1980 is dominated by two empirical orthogonal function (EOF) modes: the “tilt” mode, having opposite signs in the eastern and western equatorial Pacific and in phase with zonal wind forcing and El Niño–Southern Oscillation (ENSO) indices, and a second EOF mode of one sign across the Pacific. Because the tilt mode is of opposite sign in the eastern and western equatorial Pacific while the second EOF mode is of one sign, the second mode h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 30 publications
10
48
0
Order By: Relevance
“…McPhaden (2012) noticed that the relationship between the equatorial SST and WWV changed in the first decade of the twenty-first century. Bunge and Clarke (2014) also found the same relationship in similar decadal periods (pre-1973, 1974-97, and post-1998). In our study, by calculating the lead time of maximum correlation between the WWV index and equatorial SST with a 5-month running mean, we identify roughly three periods, 1960-76, 1977-99, and 2000-10, with the first and last periods showing reduced WWV lead (7-month lead for 1960-76 and 4-month lead for 2000-10) over ENSO compared to the period in between (9-month lead).…”
Section: Summary and Discussionsupporting
confidence: 67%
“…McPhaden (2012) noticed that the relationship between the equatorial SST and WWV changed in the first decade of the twenty-first century. Bunge and Clarke (2014) also found the same relationship in similar decadal periods (pre-1973, 1974-97, and post-1998). In our study, by calculating the lead time of maximum correlation between the WWV index and equatorial SST with a 5-month running mean, we identify roughly three periods, 1960-76, 1977-99, and 2000-10, with the first and last periods showing reduced WWV lead (7-month lead for 1960-76 and 4-month lead for 2000-10) over ENSO compared to the period in between (9-month lead).…”
Section: Summary and Discussionsupporting
confidence: 67%
“…We also found that the instantaneous WWV contribution is dominant during the post‐2000 period, which is consistent with the post‐2000 increase of the influence of the tilt‐mode in explaining WWV changes (Bunge & Clarke, ), and which reduces the oscillatory nature of ENSO as the weaker adjusted postevent WWV changes are overpowered by the instantaneous contribution (Figure b). Furthermore, the reduced influence of adjusted WWV contributions during this period explains the observed shortening of WWV versus ENSO SST lead time to two to three months (Figure ) (Bunge & Clarke, ; Horii et al, ; McPhaden, ). This reduced adjusted WWV contribution influence was most prominently found in the recharged phase, which leaves the instantaneous WWV contribution almost solely responsible for the recharged phase (Figures c and f).…”
Section: Discussionmentioning
confidence: 95%
“…The two questions raised by this study are as follows: (1) What causes the recharged periods being dominated by the instantaneous response and the discharged periods being dominated by the adjusted response and (2) why has the adjusted WWV response changed in the post‐2000 period, while the instantaneous WWV response has not, given that both responses are forced by the same wind events. This might be due to (i) changes to the structure of wind events between these two periods (Harrison & Chiodi, ) or (ii) the post‐2000 westward shift of the Bjerknes feedback region (Bunge & Clarke, ; Hu et al, ). Additionally, we speculate that off‐equatorial winds (between 5°N–15°N and 5°S–15°S), which have a large instantaneous WWV contribution and a much smaller adjusted response (McGregor et al, ), play a crucial role in answering this question.…”
Section: Discussionmentioning
confidence: 99%
“…The region of relatively low correlation near Kanton Island is, in turn, related with the misplacement of the pivot point in the model, a topic we return to in section 3.3. At Christmas Island, the model has skill at capturing events, especially in the ERA‐40 experiment, but generally underestimates the amplitude, consistent with Figure in Zhu et al () (in particular, compare their Figures a and b). Interestingly, the region of reduced correlation near Kanton Island is also the region in which Bunge and Clarke () argue that the relationship between variations in sea surface height and the depth of the 20°C isotherm is obscured by the influence of rainfall. These authors note the importance of zonal advective processes in this region (see also Dewitte et al, ), processes that are missing from the multimode model and which Zhu et al () argue contribute to the reduced performance of their model in this region.…”
Section: Resultsmentioning
confidence: 99%